2020
DOI: 10.3390/polym12112573
|View full text |Cite
|
Sign up to set email alerts
|

The Transferability and Design of Commercial Printer Settings in PLA/PBAT Fused Filament Fabrication

Abstract: In many fused filament fabrication (FFF) processes, commercial printers are used, but rarely are printer settings transferred from one commercial printer to the other to give similar final tensile part performance. Here, we report such translation going from the Felix 3.0 to Prusa i3 MK3 printer by adjusting the flow rate and overlap of strands, utilizing an in-house developed blend of polylactic acid (PLA) and poly(butylene adipate-co-terephthalate) (PBAT). We perform a sensitivity analysis for the Prusa prin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…The results of the tension tests for the CF/PDMS samples showed a decrease in the elongation, ultimate strength, and toughness, but an increase in the Young’s Modulus with increasing CF loadings. Microscopic investigation in previous works showed that holes, voids, and other defects are formed by moving CFs in the PDMS polymer matrix when stress was applied to the material [ 44 , 47 ]. The accumulation of these defects in the CF-containing samples likely caused the sample to break before reaching the same ultimate strength and elongation as the PDMS pristine.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the tension tests for the CF/PDMS samples showed a decrease in the elongation, ultimate strength, and toughness, but an increase in the Young’s Modulus with increasing CF loadings. Microscopic investigation in previous works showed that holes, voids, and other defects are formed by moving CFs in the PDMS polymer matrix when stress was applied to the material [ 44 , 47 ]. The accumulation of these defects in the CF-containing samples likely caused the sample to break before reaching the same ultimate strength and elongation as the PDMS pristine.…”
Section: Resultsmentioning
confidence: 99%
“…Felix reference curve in black. With f‐o rate 110%–25%, this curve can be approached; (b) diagram of strands/rasters in the tensile bar simulated with varying nozzle diameter; (C) influence of d nozzle and v print on (A) mass, (B) width, and (C) thickness of PLA@PBAT printed at 210°C and (d–f) comparison to the results of samples printed at 230 C with fixed LT 0.15 mm; (D) (a) PLA@PBAT viscosity based on shear rate and melt flow index (MFI) measured at varying temperatures; (b) DSC curves of specimens 42 …”
Section: Additive Manufacturing Of Pla Composites Via 3‐dpt Fused Fil...mentioning
confidence: 99%
“…Wang et al. [ 247 ] produced blends with different PLA/PHB weight ratios, ranging from 20/80 to 80/20, and then obtained filaments for FDM and studied their thermal and mechanical properties. The presence of PHB permitted to print the blends at a lower temperature (190 °C) than pure PLA (210 °C), due to a decrease in the flow index values.…”
Section: Polyester‐based Blendsmentioning
confidence: 99%
“…Better results also in terms of mechanical properties (elongation at break) were found for 80/20 PLA/PHB blends. [ 247 ] Ecker et al. [ 248 ] used the same PLA/PHA ratio, but they employed a proprietary PHA copolymer instead of PHB.…”
Section: Polyester‐based Blendsmentioning
confidence: 99%
See 1 more Smart Citation